Pengaruh Ukuran Perusahaan, Likuiditas dan Profitabilitas terhadap Kebijakan Hutang pada Perusahaan Pertambangan - Vitryani Tarigan; Djuli Sjafei Purba; Sri Martina (Owner : Riset dan Jurnal Akuntansi, 2022)
The increasingly competitive business world presents many challenges for the business world, one of which is financing. Most companies choose loans because they use them to get tax savings on company profits. So far, mining companies in Indonesia have continued to experience a decline in the development phase. Due to the ups and downs of mining, mining companies often carry out debt policies as a way to finance company operations in the hope of increasing profits or otherwise providing risk. Debt can also increase the value of the company if used properly. This study aims to determine the effect of company size, liquidity and profitability on debt policy in mining companies listed on the Indonesia Stock Exchange in 2018-2020. Several previous studies on debt policy have different results. Therefore, other research needs to be done to retest the theory of debt policy. The population of this research is 46 mining companies. The sampling method used was purposive sampling method, so that 18 sample companies were obtained for 3 years of observation (2018-2020) with 54 observations (observations). The research data was obtained from a sample of companies downloaded from the Indonesia Stock Exchange website. The data analysis technique used is multiple regression analysis. The process of data analysis that is carried out first is the classical assumption test, multiple analysis and then hypothesis testing. The results of the study that profitability has a negative and significant effect on debt policy, liquidity has a negative and significant effect on debt policy and firm size has a negative and insignificant effect on debt policy.